The Visible and the Invisible Hilary Mantel - Pollard, Eileen J. (My University, 2016)
This talk addresses the scarcity of critical material on Hilary Mantel’s writing in the academy. It questions the suitability of the ‘origin’ paradigm within the criticism that is available, which closes off the excess of Mantel’s texts through attempts to ‘unite’ her corpus. The ambiguity of her writing, and its suspicions, suggest Jacques Derrida’s thought as a pertinent means to read the differences in her work differently. The proximity of Jean-Luc Nancy’s philosophy with Derrida’s thought allows the significance of ellipsis to surface as a liberating catalyst for weaving the implications of Derrida’s thinking through the writing of Mantel. This synthesis constitutes an original combination because Mantel’s writing has not been closely studied, Derrida’s notion of ellipsis has been eclipsed by philosophy, and the combination of these two ‘invisibilities’ is seminal. The talk begins with an exploration of the mythologies I discovered and interrogated during the course of my thesis. It then considers the key points in Mantel’s writing career. In particular taking her from the difficulty and invisibility of 1979 when A Place of Greater Safety, her first novel, was rejected, to winning the Booker prize twice in succession in 2009 and 2012. It thereby traces the story of her shift from invisible to infamous, in terms of her treatment by the mainstream British media as well as her phenomenal post-millennium success.
Keywords: Mantel, Hilary -- Crítica e interpretación